Differences Between Classical and Group Methods on Student's Qur'anic Reading Skill at the Al-Quran Education Center (TPA) Musala Jirek, Padang Ganting Disctrict, Tanah Datar Regency - Rahmatul Fauzia; Jamaris Jamaris (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This study aims to see the description and differences between the classical and group methods on the ability to read the Qur'an in students at the Al-Qur'an Education Park (TPA) Musala Jirek Kec. Padang Ganting Tanah Datar. The type of research used by the researcher is using a quantitative approach with the type of experimental method. The population in this study was recorded as santri and some students who were still actively reading the Qur'an at the TPA Musala Jirek during the COVID-19 period with a total of 16 students. The sample in this study was the experimental group I using the Classical Method and the experimental group II. Each group opened 6 people. The research instrument is a performance questionnaire test. The data analysis technique used is the normality test and homogeneity test. The results of the calculation of the classical and group methods on the ability to read the Qur'an. The results showed that the ability to read the Qur'an in students using the Classical Method was better with an average of 84.62 compared to learning using the group method with an average of 81.72. So, it can be said that there is a significant difference between the Classical Method and the Al-Qur'an Reading Ability Group for Santri at the Al-Qur'an Education Park (TPA) Musala Jirek Kec. Padang Ganting Tanah Datar.Keywords: Classical Method, Group, Al Qur'an